Method for measuring water absorption rate of machine-made sand

By combining apparent density measurement and water repellent treatment technology, the existing problems of complexity and low accuracy of the water absorption test method of the machined sand are solved, and higher testing accuracy and reliability are achieved.

CN119779901AInactive Publication Date: 2025-04-08HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411940185.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing water absorption test method for machined sand is complex in operation, low in accuracy, and has problems of manual subjective judgment and sample loss, which affects the reliability and consistency of the test results.

Method used

The test method based on the combination of apparent density differences and hydrophobic treatment is adopted to determine the apparent density of the machined sand by weighing and drainage methods, and the water absorption rate of computerized sand is combined with the water repellent treatment technology.

Benefits of technology

It improves the accuracy and repetition of the test, reduces the impact of human subjective judgment, shortens the test time, and ensures the reliability and applicability of the results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119779901A_ABST
    Figure CN119779901A_ABST
Patent Text Reader

Abstract

The invention discloses a method for measuring the water absorption rate of machine-made sand and belongs to the technical field of building materials. The invention aims to solve the problems of low efficiency and poor accuracy of the current standard method for testing the water absorption rate of the medium sand. The method comprises the following steps: firstly, drying machine-made sand in a drying oven to a constant amount, and then screening through a standard sieve to obtain accurate sample quality. The apparent density of one part of the sample is measured through a drainage method in an untreated state, and the other part of the sample is treated by an organic silicon water repellent and then is measured in the same way. By comparing the apparent density difference of the machine-made sand before and after hydrophobic treatment, the water absorption rate of the machine-made sand can be accurately calculated. The introduction of the volumetric water absorption effectively avoids the problem of unstable surface state control in the traditional mass water absorption, and enhances the reliability and repeatability of the result. According to the invention, the test process is simplified, the data accuracy is improved, the method is suitable for machine-made sand with various particle sizes, and a more reliable material performance evaluation tool is provided for building and infrastructure engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to a method for determining the water absorption rate of machine-made sand. Background Art

[0002] When building materials are exposed to a humid environment or eroded by water, their water absorption rate directly affects the physical properties and durability of the materials. The water absorption rate of machine-made sand determines the amount of water used in the concrete mix, which has a direct impact on the fluidity, strength and durability of the concrete. Therefore, accurately testing the water absorption rate of machine-made sand is an important part of ensuring the quality of the project and the long-term stability of the building. Especially in construction projects such as water conservancy projects and bridge foundations that have strict requirements on material properties, the evaluation of the water absorption performance of machine-made sand is particularly important.

[0003] The existing sand water absorption test method is mainly based on the saturated surface dry water absorption test specified in GB / T 14684-2022 "Construction Sand". Through drying, soaking, weighing and other operations, the mass change when water absorption is saturated is calculated. However, this method has obvious defects in practical applications. First of all, the test operation is complicated and cumbersome, and usually requires manual repeated processing of samples, such as filling, soaking and sampling, which is time-consuming and easy to cause sample loss or external interference, affecting the test accuracy. In addition, the traditional method has a certain subjectivity in judging the state of sand. For example, the judgment of the saturated surface dry state mainly relies on manual observation. This method has a large subjectivity and it is difficult to obtain highly accurate and consistent results. Furthermore, the existing testing device is usually simple in structure and needs to rely on manual operation, which not only increases the labor intensity of the operator, but also easily causes sample loss or contamination during the filling process, thereby affecting the final test results. To solve these limitations, the present invention proposes a sand water absorption test method based on the combination of apparent density difference and hydrophobic treatment. By hydrophobic treatment of sand samples and then measuring the water absorption, the water absorption performance of machine-made sand can be accurately evaluated in a more scientific way. This method not only improves the accuracy and repeatability of the test, but also greatly shortens the test time. It has important application value and urgent promotion needs. Summary of the invention

[0004] The purpose of the present invention is to solve the problem that the current standard test method for the water absorption rate of medium sand is low in efficiency and poor in accuracy, and to provide a method for measuring the water absorption rate of machine-made sand.

[0005] A method for determining the water absorption rate of machine-made sand is specifically completed in the following steps:

[0006] 1. Weigh the mass of the machine-made sand in an absolutely dry state and test the apparent density ρ0 of the machine-made sand based on the drainage method;

[0007] 2. The surface of the absolutely dry machine-made sand is treated with water repellency. After the water repellent is solidified, a layer of water repellent film is wrapped on the surface of the machine-made sand to obtain water repellent machine-made sand. The apparent density ρˊ0 of the water repellent machine-made sand is tested based on the drainage method.

[0008] 3. Based on the apparent density ρ0 and ρˊ0 of the machine-made sand before and after water repellency, the water absorption rate w of the machine-made sand is calculated according to the following formula;

[0009]

[0010] The w calculated according to the formula is the water absorption rate of machine-made sand.

[0011] Compared with the test method in the existing standard, the beneficial effects of the present invention are:

[0012] (1) The present invention proposes an improved method for testing the water absorption of machine-made sand. Compared with the existing standard method, the present invention has significant technical advantages. First, the present invention optimizes the cumbersome steps in the traditional water absorption test method, introduces hydrophobic treatment technology, and combines the drainage method to determine the apparent density. This method not only reduces the influence of human subjective judgment and improves the accuracy of the test, but also significantly reduces the labor intensity. After hydrophobic treatment, the apparent density test of machine-made sand can more comprehensively reflect the internal pore structure of the sand body and its ability to absorb water, thereby making the calculation results of water absorption more scientific and accurate. In addition, by introducing the indicator of volume water absorption, the present invention effectively overcomes the influence of unstable control of the surface state of the sand sample in the traditional mass water absorption calculation, ensuring the reliability and reproducibility of the test results. During the test process, a special hydrophobic agent and uniform spraying technology were used to ensure the uniform treatment of the machine-made sand sample, making the entire test process simple and standardized, and convenient for promotion and use in different laboratories.

[0013] (2) The present invention has also made improvements in the design of test equipment and experimental procedures to further improve efficiency and adaptability. By adding automated and semi-automated experimental devices, the need for manual intervention is reduced, errors in the immersion and sampling processes are avoided, and the experimental time is significantly shortened. The traditional method requires long-term immersion and manual judgment of the dry state of the saturated surface. The present invention replaces this subjective judgment with automatic determination of the apparent density, ensuring that the experimental results are more stable and accurate. In addition, the present invention has also expanded the applicability of the test method, and is suitable for machine-made sand of different particle sizes, especially when testing machine-made sand containing fine particles. The present invention not only solves the problems of complex operation and large result errors in the traditional water absorption test method, but also greatly improves the efficiency and accuracy of the test, providing a more reliable quality assurance for the use of machine-made sand in engineering. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a diagram of the device used for the hydrophobic treatment in Example 1, wherein 1 is a suction filtration bottle, 2 is a funnel, 3 is a vacuum pump, 4 is a spray pot filled with a hydrophobic agent, and 5 is a glass rod. DETAILED DESCRIPTION

[0015] Specific implementation method 1: This implementation method is a method for determining the water absorption rate of machine-made sand, which is specifically completed in the following steps:

[0016] 1. Weigh the mass of the machine-made sand in an absolutely dry state and test the apparent density ρ0 of the machine-made sand based on the drainage method;

[0017] 2. The surface of the absolutely dry machine-made sand is treated with water repellency. After the water repellent is solidified, the surface of the machine-made sand is coated with a layer of water repellent film to obtain water repellent machine-made sand. The apparent density ρ′0 of the water repellent machine-made sand is tested based on the drainage method.

[0018] 3. Based on the apparent density ρ0 and ρ′0 of the machine-made sand before and after water repellency, the water absorption rate w of the machine-made sand is calculated according to the following formula;

[0019]

[0020] The w calculated according to the formula is the water absorption rate of machine-made sand.

[0021] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the absolutely dry state of the machine-made sand described in step 1 means that the machine-made sand is placed in an oven at a temperature of 100°C to 110°C and dried to a constant weight, and then manually sieved with a standard square hole sieve with a pore size of 0.6mm after cooling to room temperature to remove particles smaller than 0.6mm. The other steps are the same as those in specific implementation method 1.

[0022] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the method for testing the apparent density ρ0 of machine-made sand based on the drainage method described in step one is specifically completed according to the following steps:

[0023] ①. Weigh the mass of the absolutely dry machine-made sand to an accuracy of 0.01 g and record it as m i0 ; Put the weighed machine-made sand into a 500mL volumetric flask, inject cold water to the mark close to 500mL, stir continuously to make the machine-made sand shake fully, remove bubbles, plug the bottle cap tightly, let it stand for a while, then use a dropper to add water to the 500mL mark of the volumetric flask, plug the bottle cap tightly; wipe off the water outside the volumetric flask, and then weigh its mass, accurate to 0.01g, recorded as m i1 ;

[0024] ② Pour out the water and machine-made sand in the volumetric flask in step ①, clean the volumetric flask, and then inject cold water into the volumetric flask to the 500mL mark. Plug in the stopper, wipe off the water outside the flask, and weigh its mass to an accuracy of 0.01g, which is recorded as m i2 ;

[0025] ③. According to formula (1), calculate the apparent density ρ0 of the sand, accurate to 0.01g / cm 3 ;

[0026]

[0027] Where:

[0028] ρ0—apparent density of machine-made sand, unit: g / cm 3 ;

[0029] ρ w —Density of water, in g / cm 3 ;

[0030] m i0 —Weigh the mass of the machine-made sand in an absolutely dry state, in g;

[0031] m i1 —Weigh the total mass of the absolutely dry machine-made sand, water and volumetric flask in g;

[0032] m i2 —Total mass of water and volumetric flask, in g;

[0033] α t —Correction coefficient of the effect of water temperature on apparent density; when the water temperature is 15℃, 16℃, 17℃, 18℃, 19℃, 20℃, 21℃, 22℃, 23℃, 24℃, 25℃, α t The steps are 0.002, 0.003, 0.003, 0.004, 0.004, 0.005, 0.005, 0.006, 0.006, 0.007, and 0.008, respectively. The other steps are the same as those in the first or second embodiment.

[0034] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the temperature of the cold water in step ① and step ② is 10° C. to 20° C., and the stirring time in step ① is 1 min to 2 min. The other steps are the same as those in specific embodiments 1 to 3.

[0035] Specific implementation method 5: This implementation method is different from specific implementation methods 1 to 4 in that the standing time in step ① is 48 hours to 50 hours. The other steps are the same as those in specific implementation methods 1 to 4.

[0036] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the hydrophobic treatment described in step 2 is specifically completed according to the following steps:

[0037] A single layer of absolutely dry machine-made sand is evenly spread on the filter paper on the surface of the Büchner funnel, and then a water repellent is evenly sprayed on the surface of the machine-made sand using a spray bottle, and the machine-made sand is turned over while vacuum filtering the Büchner funnel to obtain machine-made sand wrapped with a layer of water repellent film, and the machine-made sand is left to stand for a period of time at room temperature to solidify the surface water repellent agent, thereby obtaining water repellent machine-made sand. The other steps are the same as those in the first to fifth embodiments.

[0038] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the standing time is 48h to 50h; the water repellent is an organic silicon water repellent, the main component of which is isobutyl triethoxysilane, purchased from Beijing Mengtai Weiye Building Materials Co., Ltd.; the mass ratio of the water repellent to the mass of the machine-made sand in the absolute dry state is (0.3 to 0.5): (45 to 55). The other steps are the same as those of specific embodiments 1 to 6.

[0039] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the apparent density ρ′0 of the hydrophobic machine-made sand based on the drainage method described in step 2 is specifically completed in the following steps:

[0040] ①. Weigh the mass of the hydrophobic machine-made sand to an accuracy of 0.01g and record it as m' i0 ; Put the weighed machine-made sand into a 500mL volumetric flask, add cold water to the mark close to 500mL, stir continuously to make the machine-made sand shake fully, remove bubbles, plug the bottle cap tightly, let it stand for a while, then use a dropper to add water to the 500mL mark of the volumetric flask, plug the bottle cap tightly; wipe off the water outside the volumetric flask, and then weigh its mass, accurate to 0.01g, recorded as m′ i1 ;

[0041] ② Pour out the water and machine-made sand in the volumetric flask in step ①, clean the volumetric flask, and then inject cold water into the volumetric flask to the 500mL mark. Plug in the stopper, wipe off the water outside the flask, and weigh its mass to an accuracy of 0.01g, which is recorded as m′ i2 ;

[0042] ③. Calculate the apparent density ρ′0 of the hydrophobic machine-made sand according to formula (2), accurate to 0.01 g / cm 3 ;

[0043]

[0044] Where:

[0045] ρ′0——apparent density of hydrophobic machine-made sand, unit: g / cm 3 ;

[0046] ρ′ w ——Density of water, unit: g / cm 3 ;

[0047] m′ i0 ——Weigh the mass of the machine-made sand after water repellency, in g;

[0048] m′ i1 ——The total mass of the hydrophobic machine-made sand, water and volumetric flask, in g;

[0049] m′ i2 ——Total mass of water and volumetric flask, in g;

[0050] α t ——Correction coefficient of the effect of water temperature on apparent density. When the water temperature is 15℃, 16℃, 17℃, 18℃, 19℃, 20℃, 21℃, 22℃, 23℃, 24℃, 25℃, α t The order is 0.002, 0.003, 0.003, 0.004, 0.004, 0.005, 0.005, 0.006, 0.006, 0.007, and 0.008. The other steps are the same as those in the first to seventh embodiments.

[0051] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the temperature of the cold water in step ① and step ② is 10°C to 20°C; the stirring time in step ① is 1min to 2min; the standing time in step ① is 0.5h to 1h. The other steps are the same as those in specific embodiments 1 to 8.

[0052] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the water absorption rate w in step 3 refers to the volume water absorption rate, that is, the percentage of the volume of absorbed water to the volume of the material in its natural state. The other steps are the same as specific embodiments 1 to 9.

[0053] The following examples are used to verify the beneficial effects of the present invention:

[0054] Embodiment 1: A method for determining the water absorption rate of machine-made sand is specifically completed according to the following steps:

[0055] 1. Dry 300g of machine-made sand in an oven at 105℃ to a constant weight. After cooling to room temperature, manually screen it with a standard square hole sieve with an aperture of 0.6mm to remove particles smaller than 0.6mm to obtain machine-made sand in an absolutely dry state. Weigh the mass of the machine-made sand in an absolutely dry state, and test the apparent density ρ0 of the machine-made sand based on the drainage method.

[0056] The method for testing the apparent density ρ0 of machine-made sand based on the drainage method described in step 1 is specifically completed in the following steps:

[0057] ①. Weigh the mass of the absolutely dry machine-made sand to an accuracy of 0.01 g and record it as m i0 , m i0 =52.36g; put the weighed machine-made sand into a 500mL volumetric flask, inject cold water at a temperature of 16℃ to the mark close to 500mL, stir continuously for 1.5min to fully shake the machine-made sand, remove bubbles, plug the bottle cap, let it stand for 48h, then use a dropper to add water to the 500mL mark of the volumetric flask, plug the bottle cap; wipe off the water outside the volumetric flask, and then weigh its mass to an accuracy of 0.01g, recorded as m i1, m i1 =598.19g;

[0058] ② Pour out the water and machine-made sand in the volumetric flask in step ①, clean the volumetric flask, and then fill the volumetric flask with cold water at a temperature of 16℃ to the 500mL mark. Plug in the bottle stopper, wipe off the water outside the bottle, and weigh its mass to an accuracy of 0.01g, which is recorded as m i2 , m i2 =564.00g;

[0059] ③. According to formula (1), calculate the apparent density ρ0 of the sand, accurate to 0.01g / cm 3 , after calculation, we know that ρ0 is 2.88g / cm 3 ;

[0060]

[0061] Where:

[0062] ρ0—apparent density of machine-made sand, unit: g / cm 3 ;

[0063] ρ w —Density of water, in g / cm 3 , specifically 1g / cm 3 ;

[0064] m i0 —Weigh the mass of the machine-made sand in an absolutely dry state, in g;

[0065] m i1 —Weigh the total mass of the absolutely dry machine-made sand, water and volumetric flask in g;

[0066] m i2 —Total mass of water and volumetric flask, in g;

[0067] α t —Correction coefficient for the effect of water temperature on apparent density; since the water temperature is 16°C, α t is 0.003;

[0068] 2. The surface of the absolutely dry machine-made sand is treated with water repellency. After the water repellent is solidified, the surface of the machine-made sand is coated with a layer of water repellent film to obtain water repellent machine-made sand. The apparent density ρ′0 of the water repellent machine-made sand is tested based on the drainage method.

[0069] The hydrophobic treatment described in step 2 is specifically completed according to the following steps:

[0070] A single layer of absolutely dry machine-made sand is evenly spread on the filter paper on the surface of the Büchner funnel, and then a water repellent is evenly sprayed on the surface of the machine-made sand using a spray bottle. The machine-made sand is turned over while the Büchner funnel is vacuum filtered to obtain machine-made sand wrapped with a layer of water repellent film, and then allowed to stand at room temperature for 48 hours to solidify the surface water repellent to obtain water-repellent machine-made sand; the water repellent is an organosilicon water repellent, the main component of which is isobutyltriethoxysilane, purchased from Beijing Mengtai Weiye Building Materials Co., Ltd.; the mass ratio of the water repellent to the mass of the absolutely dry machine-made sand is 0.4:51;

[0071] The apparent density ρ′0 of the water-repellent machine-made sand based on the drainage method described in step 2 is specifically completed in the following steps:

[0072] ①. Weigh the mass of the hydrophobic machine-made sand to an accuracy of 0.01g and record it as m' i0 , m′ i0 =51.81g; put the weighed machine-made sand into a 500mL volumetric flask, inject cold water at a temperature of 16℃ to the mark close to 500mL, stir continuously for 1min to fully shake the machine-made sand, remove bubbles, plug the bottle cap, let it stand for 0.5h, then use a dropper to add water to the 500mL mark of the volumetric flask, plug the bottle cap tightly; wipe off the water outside the volumetric flask, and then weigh its mass, accurate to 0.01g, recorded as m′ i1 , m′ i1 =596.63g;

[0073] ② Pour out the water and machine-made sand in the volumetric flask in step ①, clean the volumetric flask, and then fill the volumetric flask with cold water at a temperature of 16℃ to the 500mL mark, plug the bottle tightly, wipe off the water outside the bottle, and weigh its mass to an accuracy of 0.01g, which is recorded as m′ i2 , m′ i2 =564g;

[0074] ③. Calculate the apparent density ρ′0 of the hydrophobic machine-made sand according to formula (2), accurate to 0.01 g / cm 3 , after calculation, we know that: ρ′0=2.70g / cm3 ;

[0075]

[0076] Where:

[0077] ρ′0——apparent density of hydrophobic machine-made sand, unit: g / cm 3 ;

[0078] ρ′ w ——Density of water, unit: g / cm 3 , specifically 1g / cm 3 ;

[0079] m′ i0 ——Weigh the mass of the machine-made sand after water repellency, in g;

[0080] m′ i1 ——The total mass of the hydrophobic machine-made sand, water and volumetric flask, in g;

[0081] m′ i2 ——Total mass of water and volumetric flask, in g;

[0082] α t —Correction coefficient for the effect of water temperature on apparent density; since the water temperature is 16°C, α t is 0.003;

[0083] 3. Based on the apparent density ρ0 and ρ′0 of the machine-made sand before and after water repellency, the water absorption rate w of the machine-made sand is calculated according to formula (3). After calculation, it can be found that: w1 = 0.86%;

[0084]

[0085] The w calculated according to formula (3) is the water absorption rate of machine-made sand.

[0086] Embodiment 2: The difference between this embodiment and embodiment 1 is: i0 =48.15g; m i1 =601.70g; m i2 =570.27g; m' i0 =53.31g; m' i1 =603.72g, m' i2 =570.27g; after calculation, we know that: ρ0 = 2.88g / cm 3 ; ρ′0=2.68g / cm 3 ; w2 = 0.94%. Other steps and parameters are the same as those in Example 1.

[0087] Embodiment 3: The difference between this embodiment and embodiment 1 is:i0 =50.58g; m i1 =584.67g, m i2 =551.58g; m' i0 =49.46g; m' i1 =582.70g, m' i2 =551.58g; after calculation, we know that: ρ0 = 2.89g / cm 3 , ρ′0=2.70g / cm 3 , w3=0.93%. Other steps and parameters are the same as those in Example 1.

[0088] The water absorption rate is the arithmetic mean of the three water absorption rate results of Examples 1-3, w average value = 0.91%.

Claims

1. A method for determining the water absorption rate of machine-made sand, characterized in that The determination method is specifically completed according to the following steps:

1. Weigh the mass of the machine-made sand in an absolutely dry state and test the apparent density ρ0 of the machine-made sand based on the drainage method; 2. The surface of the absolutely dry machine-made sand is treated with water repellency. After the water repellent is solidified, the surface of the machine-made sand is coated with a layer of water repellent film to obtain water repellent machine-made sand. The apparent density ρ′0 of the water repellent machine-made sand is tested based on the drainage method.

3. Based on the apparent density ρ0 and ρ′0 of the machine-made sand before and after water repellency, the water absorption rate w of the machine-made sand is calculated according to the following formula; The w calculated according to the formula is the water absorption rate of machine-made sand.

2. The method for determining the water absorption rate of machine-made sand according to claim 1, characterized in that The absolutely dry state of the machine-made sand described in step 1 means: placing the machine-made sand in an oven at a temperature of 100°C to 110°C and drying it to a constant weight, cooling it to room temperature, and then manually sieving it with a standard square hole sieve with a pore size of 0.6mm to remove particles smaller than 0.6mm.

3. The method for determining the water absorption rate of machine-made sand according to claim 1, characterized in that The method for testing the apparent density ρ0 of machine-made sand based on the drainage method described in step 1 is specifically completed in the following steps: ①. Weigh the mass of the absolutely dry machine-made sand to an accuracy of 0.01 g and record it as m i0 ; Put the weighed machine-made sand into a 500mL volumetric flask, inject cold water to the mark close to 500mL, stir continuously to make the machine-made sand shake fully, remove bubbles, plug the bottle cap tightly, let it stand for a while, then use a dropper to add water to the 500mL mark of the volumetric flask, plug the bottle cap tightly; wipe off the water outside the volumetric flask, and then weigh its mass, accurate to 0.01g, recorded as m i1 ; ② Pour out the water and machine-made sand in the volumetric flask in step ①, clean the volumetric flask, and then inject cold water into the volumetric flask to the 500mL mark. Plug in the stopper, wipe off the water outside the flask, and weigh its mass to an accuracy of 0.01g, which is recorded as m i2 ; ③. According to formula (1), calculate the apparent density ρ0 of the sand, accurate to 0.01g / cm 3 ; Where: ρ0—apparent density of machine-made sand, unit: g / cm 3 ; ρ w —Density of water, in g / cm 3 ; m i0 —Weigh the mass of the machine-made sand in an absolutely dry state, in g; m i1 —Weigh the total mass of the absolutely dry machine-made sand, water and volumetric flask in g; m i2 —Total mass of water and volumetric flask, in g; α t —Correction coefficient of the effect of water temperature on apparent density; when the water temperature is 15℃, 16℃, 17℃, 18℃, 19℃, 20℃, 21℃, 22℃, 23℃, 24℃, 25℃, α t They are 0.002, 0.003, 0.003, 0.004, 0.004, 0.005, 0.005, 0.006, 0.006, 0.007, and 0.008 respectively.

4. The method for determining the water absorption rate of machine-made sand according to claim 3, characterized in that The temperature of the cold water in step ① and step ② is 10° C. to 20° C.; the stirring time in step ① is 1 min to 2 min.

5. The method for determining the water absorption rate of machine-made sand according to claim 3, characterized in that The standing time described in step ① is 48h~50h.

6. The method for determining the water absorption rate of machine-made sand according to claim 1, characterized in that The hydrophobic treatment described in step 2 is specifically completed according to the following steps: Evenly spread a single layer of absolutely dry machine-made sand on the filter paper on the surface of the Büchner funnel, and then use a spray bottle to evenly spray the water-repellent agent on the surface of the machine-made sand. While turning the machine-made sand, vacuum filter the Büchner funnel to obtain machine-made sand wrapped with a layer of water-repellent film. Let it stand at room temperature for a period of time to solidify the surface water-repellent agent to obtain water-repellent machine-made sand.

7. The method for determining the water absorption rate of machine-made sand according to claim 6, characterized in that The standing time is 48h to 50h; the water repellent is an organic silicon water repellent, the main component of which is isobutyltriethoxysilane; the mass ratio of the water repellent to the mass of the absolutely dry machine-made sand is (0.3 to 0.5):(45 to 55).

8. The method for determining the water absorption rate of machine-made sand according to claim 1, characterized in that The apparent density ρ′0 of the water-repellent machine-made sand based on the drainage method described in step 2 is specifically completed in the following steps: ①. Weigh the mass of the hydrophobic machine-made sand to an accuracy of 0.01g and record it as m' i0 ; Put the weighed machine-made sand into a 500mL volumetric flask, add cold water to the mark close to 500mL, stir continuously to make the machine-made sand shake fully, remove bubbles, plug the bottle cap tightly, let it stand for a while, then use a dropper to add water to the 500mL mark of the volumetric flask, plug the bottle cap tightly; wipe off the water outside the volumetric flask, and then weigh its mass, accurate to 0.01g, recorded as m′ i1 ; ② Pour out the water and machine-made sand in the volumetric flask in step ①, clean the volumetric flask, and then inject cold water into the volumetric flask to the 500mL mark. Plug in the stopper, wipe off the water outside the flask, and weigh its mass to an accuracy of 0.01g, which is recorded as m′ i2 ; ③. Calculate the apparent density ρ′0 of the hydrophobic machine-made sand according to formula (2), accurate to 0.01 g / cm 3 ; Where: ρ′0——apparent density of hydrophobic machine-made sand, unit: g / cm 3 ; ρ′ w ——Density of water, unit: g / cm 3 ; m′ i0 ——Weigh the mass of the machine-made sand after water repellency, unit: g; m′ i1 ——The total mass of the hydrophobic machine-made sand, water and volumetric flask, in g; m′ i2 ——Total mass of water and volumetric flask, in g; α t ——Correction coefficient of the effect of water temperature on apparent density. When the water temperature is 15℃, 16℃, 17℃, 18℃, 19℃, 20℃, 21℃, 22℃, 23℃, 24℃, 25℃, α t They are 0.002, 0.003, 0.003, 0.004, 0.004, 0.005, 0.005, 0.006, 0.006, 0.007, and 0.008 respectively.

9. The method for determining the water absorption rate of machine-made sand according to claim 8, characterized in that The temperature of the cold water in step ① and step ② is 10° C. to 20° C.; the stirring time in step ① is 1 min to 2 min; and the standing time in step ① is 0.5 h to 1 h.

10. The method for determining the water absorption rate of machine-made sand according to claim 1, characterized in that The water absorption rate w described in step 3 refers to the volume water absorption rate, that is, the percentage of the volume of absorbed water to the volume of the material in its natural state.